Pecularities of formation of the linguo-cultural aspect in teaching students of a non-linguistic university in a distance format - A.V. Guzova; N.V. Savitskaya; O.V. Dedova (Язык и текст)
The work is aimed at exploring the possibilities of distance learning of a foreign language for students of non-linguistic universities. Special attention is paid to the formation of the linguistic and cultural aspect as a necessary element of students' communicative competence. The paper examines the difficulties that arise for teachers of a foreign language in the process of work, which are due to the specifics of learning conditions in a non-linguistic university, and presents possible ways to solve them in the distance learning format.